BEBAN PAJAK, NILAI TUKAR, DAN TUNNELING INCENTIVE TERHADAP TRANSFER PRICING (Studi Empiris pada Perusahaan Manufaktur di Bursa Efek Indonesia tahun 2015-2019) - Widiastuti Widiastuti; Ela Fauziah; Fikko Bangun Persada (LPPM Universitas Pelita Bangsa, 2022)
The goal of a company is to get the maximum profit, one way for the company to get a big profit, namely by strengthening strategic alliances, conducting transactions and even conducting transfer pricing practices with affiliated companies in various countries in the world. transfer pricing is an exchange, purchase or sale transaction made by multinational companies that have a special relationship. The purpose of this study was to determine the effect of exchange rate tax expense and tunneling incentives on the company's decision to carry out transfer pricing at manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019, namely as many as 189 companies with purposive sampling technique and resulted in 27 company samples to be tested. The analysis technique used is multiple regression analysis. The results showed that (1) the tax burden has a significant negative effect on transfer pricing with a value of β -0.240 and a significance value of 0.041, (2) the exchange rate has a significant negative effect on transfer pricing with a value of β -0.293 and a significance value of 0.030, (3) tunneling Incentive has a significant negative effect on transfer pricing with a value of β -1.105 and a significance value of 0.000. Simultaneous results in this analysis show that the variavels of tax burden, exchange rates and tunneling incentives have an effect on transfer pricing with a significance value of 0.000. Keywords: Transfer Pricing, Tax Expenses, Exchange Rates, Tunneling Incentive